Analisis Perilaku Masyarakat Dalam Pencegahan Malaria - Landi, Melkisedek; Radandima, Ester (Poltekkes Kemenkes Kupang, 2022)
Background: Malaria endemic areas are generally remote villages with inadequate environmental conditions and low levels of preventive behavior. Objectives: This research aims to determine individual, behavioral and environmental characteristics of malaria in Kambatatana Village, Pandawai District. Method: This research is descriptive correlational with a cross-sectional research design, using a sample of 60 people. Results: The results showed that the age of malaria sufferers consisted of: <18 years 36 (33.3%), 18-40 years 44 (41%), 41-60 years 19 (18%), >60 years 9 (8.3%). Occupation of sufferers: Farmer 63 (64.28%), not yet working 2 (2%), student 29 (27%) and teacher/honorary 4 (4%). Malaria cases based on examination results consisted of: Falciparum 40 (67%), Vivax 10 (17%), and Mix 10 (17%). Malaria prevention behavior: Poor 2 (3%), Fair 48 (80%), Good 10 (17%) with the highest prevention behavior being the use of mosquito nets (3.2). Environmental conditions: Poor 40 (67%), Fair 18 (30%), Good 2 (3%), with 95% bushy environment, 25 (42%) near swamps, 52 (87%) do not have wires for ventilation, 48 (80%) had low light, and 45 (75%) had poor walls. The Spearman test results showed a value of 0.621, which means there is no significant relationship between the environment and malaria prevention behavior.